A leftward perceptual asymmetry when judging the attractiveness of visual patterns. Issue 1 (2nd January 2019) - Rodway, Paul; Schepman, Astrid; Crossley, Becky; Lee, Jennifer
ABSTRACT: Perceptual judgements concerning the magnitude of a stimulus feature are typically influenced more by the left side of the stimulus than by the right side. This research examined whether the leftward bias also applies to judgements of the attractiveness of abstract visual patterns. Across four experiments participants chose between two versions of a stimulus which either had an attractive left side or an attractive right side. Experiments 1 and 2 presented artworks and experiments 3 and 4 presented wallpaper designs. In each experiment participants showed a significant bias to choose the stimulus with an attractive left side more than the stimulus with an attractive right side. The leftward bias emerged at age 10/11, was not caused by a systematic asymmetry in the perception of colourfulness or complexity, and was stronger when the difference in attractiveness between the left and right sides was larger. The results are relevant to the aesthetics of product and packaging design and show that leftward biases extend to the perceptual judgement of everyday items. Possible causes of the leftward bias for attractiveness judgements are discussed and it is suggested that the size of the bias may not be a measure of the degree of hemispheric specialization.